Epithelial toxicity of alkylglycoside surfactants. Issue 1 (25th October 2012) - Vllasaliu, Driton; Shubber, Saif; Fowler, Robyn; Garnett, Martin; Alexander, Cameron; Stolnik, Snow
Abstract Alkylglycoside surfactants have been proposed as drug delivery excipients with the potential to enhance mucosal drug absorption of therapeutic macromolecules. Previous work reported their drug absorption‐promoting potential by demonstrating that several compounds within this class of surfactants improve mucosal absorption of peptides, proteins and other macromolecules. However, detailed investigation of their toxicity has not been conducted. Using Calu‐3 epithelial cell layers as a model of the airway mucosa, and liposomes as models of cell membranes, this work investigates the cytotoxicity of dodecylmaltoside, tridecylmaltoside and tetradecylmaltoside, as representative alkylglycosides. A combination of different toxicity assays and other tests indicating cell membrane disruption were used to assess cytotoxicity. The alkylglycosides tested induced a dramatic reduction in cell viability, cell membrane and liposome‐disruptive effects, as well as abrogation of transepithelial electrical resistance that did not recover completely. Importantly, these phenomena were noted at concentrations markedly lower than those typically used in the literature studies demonstrating the absorption‐enhancing properties of alkylglycosides. This work therefore demonstrates that alkylglycosides exhibit significant toxicity towards airway epithelial cells, most likely resulting from a membrane‐damaging effect, highlighting a need for further evaluation of their safety as absorption‐enhancing excipients. © 2012 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 102:114–125, 2013